2017
DOI: 10.1063/1674-0068/30/cjcp1705092
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation Dynamics of OCS at 217 nm

Abstract: The S(1 D 2)+CO(X 1 Σ +) product channel from photodissociation of OCS at 217 nm has been measured using the DC slice velocity map imaging (VMI) technique in combination with resonance enhanced multiphoton ionization (REMPI). Two different REMPI intermediate states (1 F 3 and 1 P 1) and several pump-probe laser polarization geometries are used to detect the angular momentum polarization of the photofragmented S(1 D 2). The molecularframe polarization parameters, as well as the laboratory-frame anisotropy param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Experiments are performed using our home-made DC-slice velocity map imaging setup, details of which can be found in our recent publications [15][16][17]. Briefly, a gas mixture of 1% 3-BrFPh vapor seeded in argon at a stagnation pressure of ∼3 bar is supersonically expanded into the first vacuum chamber through a pulsed nozzle (General Valve, Series 9, 0.25 mm orifice) and then skimmed by a 1 mm skimmer before entering the second differentially pumped chamber.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Experiments are performed using our home-made DC-slice velocity map imaging setup, details of which can be found in our recent publications [15][16][17]. Briefly, a gas mixture of 1% 3-BrFPh vapor seeded in argon at a stagnation pressure of ∼3 bar is supersonically expanded into the first vacuum chamber through a pulsed nozzle (General Valve, Series 9, 0.25 mm orifice) and then skimmed by a 1 mm skimmer before entering the second differentially pumped chamber.…”
Section: Experiments Detailsmentioning
confidence: 99%
“…Nevertheless, the neutral di-atomic counterpart (CO) can be fragmented with such highly populated rotational states, which arises due to rovibronically coupled strong bending forces in triatomic OCS [54]. A few reports on photodissociation and DEA to OCS [32,33,[55][56][57][58][59][60][61] reported that CO fragments are dominantly associated with highly excited rotational levels in the vibrational ground state, which confirms that CO stretching acts as a spectator in the dynamics. Our observations agree with such reports for rovibronically coupled high momentum bands.…”
mentioning
confidence: 94%